PERANCANGAN SISTEM INFORMASI SENSUS HARIAN RAWAT INAP DI RUMAH SAKIT BHAYANGKARA MATARAM - Herdiawan Ramdani; Syamsuriansyah Syamsuriansyah; Helmina Andriani (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2018)
Mataram Police Hospitals are still using manual systems in the daily distribution of course this will have an effect on health services to patients in because the data is not stored in electronic form. So that problems frequently encountered is loss of data when required return., In this case the data on mean daily reports, monthly reports and annual reports were obtained from the results of activities of daily census in each ward.   The type of design used in this research is descriptive survey. by adopting the design method is to use development system lyfe cycle (SDLC). The SDLC method has several stages of the planning phase, analysis phase, design phase, implementation phase and maintenance phase.   Results of this study resulted in the design of information systems that consist of several related tables include: Table of patients, employees Tables, Table status, profession table, table classes, table space, table hospitalization, inpatient table detail. And the results of interface design, the research ii produce several interfaces, among others: the login menu, the main menu, menu entries patients (data of employees, datastatus, the data profession, class data, the data rooms), menu transactions (inpatient, inpatient table detail ), form the admin user and report form